Erratum: Analisis Distance Covered, Heart Rate, dan Kehilangan Cairan Tubuh Diberbagai Posisi Pada Pemain Sepakbola - Muhammad Yusuf Rojali Rahmatillah; Eka Nugraha; Hamidie Ronald Daniel Ray (JUARA : Jurnal Olahraga, 2020)
Correction to: JUARA: Jurnal Olahraga This corrects the article DOI: https://doi.org/10.33222/juara.v4i2.615 This article was originally published using English metadata in the article title and this is our fault. but now the article metadata has been changed in Indonesian and appears correctly in the current article.